A Tribological Analysis of PAO-Based Hybrid SiO2-TiO2 Nanolubricants - R.N.R, Ismail; Wan Azmi, Wan Hamzah; Safril, .; N. N. M., Zawawi (IOP Publishing, 2024)
Friction and wear are caused by contact between sliding surfaces over time. It is possible to reduce friction in a compressor by improving its lubrication. The nanoparticle lubrication will aid in reducing wear and friction of the piston mechanism of the compressor. This work aims to analyse the tribology properties of performance of the system employing Polyalphaolefin (PAO)-based hybrid nanolubricants. A two-step method was used to disperse SiO2 and TiO2 nanoparticles in the PAO lubricant at volume concentrations of 0.01% and 0.05% using a two-step method. Then, hybrid nanolubricants are observed visually, and their coefficient of friction (COF) is evaluated using a four-ball tribometer. The SiO2-TiO2/PAO hybrid nanolubricants were found to have a higher than 80% sedimentation ratio up to 180 hours and to be visually stable for up to 30 days. The 0.01% SiO2-TiO2/PAO has a lower COF than the base PAO 68 oil. The 0.05%, however, does not show the expected reduction. The COF ratio for volume concentrations of 0.01% and 0.05% is 0.97 and 1.01, respectively. The highest COF reduction of nanolubricants was attained up to 2.53% at 0.01% volume concentration. Therefore, 0.01% SiO2-TiO2/PAO is the ideal condition for use and is recommended for further investigations.